Principales microorganismos que afectan al cultivo de papaya Carica papaya L. en la provincia de Los Ríos - Triguero Castro, Diego Antony (2022)
Papaya belongs to the Caricaceae family, originally from Central America, this fruit stands out for its nutritional, medicinal and flavor properties. Currently this crop has gained an important place in the demand of world consumers, being considered the third most produced tropical fruit. Papaya cultivation in the last decade has increased its production due to the high demand for this fruit in not only the national market, but also the international market, motivating many producers to dedicate themselves to this production. However, due to the lack of knowledge about this crop, it has triggered many problems, one of which is poor agronomic management and the inadequate comprehensive management of diseases of great economic importance. The global papaya industry faces major problems due to the presence of microorganisms that cause a severe imbalance in the production and quality of its fruit. Among the main microorganisms that affect this crop we have; Bacteria (Erwinia papayae) that causes bacterial necrosis of papaya, presents yellowing in the young leaves and the subsequent sample of the entire upper part of the plant. Anthracnose is a disease caused by the fungus (Colletotrichum gloeosporioides), which directly harms the quality of the postharvest fruit, causing a loss of 25 to 40%.